Template-primer binding affinity and RNase H cleavage specificity contribute to the strand transfer efficiency of HIV-1 reverse transcriptase - Luczkowiak, Joanna (J Biol Chem, 2018)
During reverse transcription of the HIV-1 genome, two strand-transfer events occur. Both events rely on the RNase H cleavage activity of reverse transcriptases (RTs) and template homology. Using a panel of mutants of HIV-1(BH10) (group M/subtype B) and HIV-1(ESP49) (group O) RTs and in vitro assays, we demonstrate that there is a strong correlation between RT minus-strand transfer efficiency and template-primer binding affinity. The highest strand transfer efficiencies were obtained with HIV-1(ESP49) RT mutants containing the substitutions K358R/A359G/S360A, alone or in combination with V148I or T355A/Q357M. These HIV-1(ESP49) RT mutants had been previously engineered to increase their DNA polymerase activity at high temperatures. Now, we found that RTs containing RNase H-inactivating mutations (D443N or E478Q) were devoid of strand transfer activity, whereas enzymes containing F61A or L92P had very low strand transfer activity. The strand transfer defect produced by L92P was attributed to a loss of template-primer binding affinity and, more specifically, to the higher dissociation rate constants (k(off)) shown by RTs bearing this substitution. Although L92P also deleteriously affected the RT's nontemplated nucleotide addition activity, neither nontemplated nucleotide addition activity nor the RT's clamp activities contributed to increased template switching when all tested mutant and WT RTs were considered. Interestingly, our results also revealed an association between efficient strand transfer and the generation of secondary cleavages in the donor RNA, consistent with the creation of invasion sites. Exposure of the elongated DNA at these sites facilitate acceptor (RNA or DNA) binding and promote template switching.